152k views
1 vote
Solve for a: 5(a+5)-3=3(2-a)

User XVargas
by
6.6k points

2 Answers

2 votes

first you do distributive property which includes

5a+25-3=6-3a

then combine like terms which is subtracting 3 from 25

5a+22=6-3a, then combine like terms by subtracting 3a from 3a and 5a

which would be 2a+22=6 then combine constants by subtracting 22 from 22 and 6 which would equal 2a =-22 answer is -11

User Johnfound
by
5.4k points
7 votes

Simplify:

5(a + 5) + -3 = 3(2 + -1a)

Reorder the terms:

5(5 + a) + -3 = 3(2 + -1a)

(5 * 5 + a * 5) + -3 = 3(2 + -1a)

(25 + 5a) + -3 = 3(2 + -1a)

Reorder the terms again:

25 + -3 + 5a = 3(2 + -1a)

Combine like terms:

]25 + -3 = 22

22 + 5a = 3(2 + -1a)

22 + 5a = (2 * 3 + -1a * 3)

22 + 5a = (6 + -3a)

Solve:

22 + 5a = 6 + -3a

To solve for variable 'a':

You have to move all terms containing A to the left, all other terms to the right.

Then add '3a' to each side of the equation:

22 + 5a + 3a = 6 + -3a + 3a

Combine like terms:

5a + 3a = 8a

22 + 8a = 6 + -3a + 3a

Combine like terms again:

-3a + 3a = 0

22 + 8a = 6 + 0

22 + 8a = 6

Add '-22' to each side of the equation.:

22 + -22 + 8a = 6 + -22

Combine like terms:

22 + -22 = 0

0 + 8a = 6 + -22

8a = 6 + -22

Combine like terms once more:

6 + -22 = -16

8a = -16

Divide each side by '8'.

a = -2

Simplify:

a = -2

Answer: a=-2

Hope I could help! :)

User Amit Kumar Gupta
by
6.6k points